MreB: unraveling the molecular mechanisms of bacterial shape, division, and environmental adaptation - Yaqi Wang; Yalan jiang; Zhixuan Song; Chengbin Zhu; Yujun Tang; Jiaofeng Peng; Peng Liu (Cell Communication and Signaling)
Abstract As a key bacterial actin-like protein, MreB plays crucial roles in maintaining cell shape, regulating peptidoglycan synthesis, and coordinating chromosome segregation, making it a promising target for novel antibiotics. This review comprehensively explores MreB’s molecular architecture, its assembly into antiparallel protofilaments, and its pivotal roles in bacterial cell morphology and division. We also delve into how MreB interacts with membrane-associated proteins such as RodZ and MreC/D to coordinate cell wall synthesis and respond to environmental signals like ion gradients and temperature changes. Furthermore, we highlight the cooperation and functional divergence between MreB and FtsZ, underscoring the evolutionary adaptability of bacterial cytoskeletal structures. The structural and functional parallels between MreB and eukaryotic cytoskeletal proteins are also examined, offering new insights into the evolution of cytoskeletal systems. By integrating insights from structural biology, synthetic biology, and microbial ecology, this review aims to provide a deeper understanding of MreB’s role in bacterial biology, its dynamic responses to environmental cues, and its implications for therapeutic innovation. This comprehensive analysis not only enhances our knowledge of bacterial self-organization mechanisms but also paves the way for the development of innovative antimicrobial strategies to address the growing challenge of antibiotic resistance.